Selection of Suitable Genotypes of Lentil (Lens culinaris Medik.) under Rainfed Conditions in South Italy Using Multi-Trait Stability Index (MTSI) - Mohamed Houssemeddine Sellami; Cataldo Pulvento; Antonella Lavini (Agronomy, 2021)
Lentil (Lens culinaris Medik.) is a popular legume crop in the Mediterranean region, widely grown for its nutritious seeds and improving soil fertility. Lentil yield is a critical and challenging trait for crop genetic improvement because it is influenced by various factors that have detrimental effects on seed yields and seed quality traits. This research was carried out in Italy between 2017 and 2019 to identify high-performing stable genotypes presenting multiple desirable traits and to assess the seed quality of 13 lentil accessions in the field. According to the results of the multi-trait stability index (MTSI), (1) only three accessions (Altamura, Easton, and Caltagirone) fared better in various environmental conditions, and (2) the selected accessions had strength toward seed yield (SY), above-ground biomass (AGB), and 1000-seed weight (THS). The genotype × environment interaction (GEI) effects were highly significant for all traits. During the third growing season, most lentil accessions were sensitive to frost. There was no correlation between lentil seed yield and protein concentration. The MTSI is a useful tool for breeders interested in selecting accessions based on their mean performance and stability, as well as desirable traits and minimum multicollinearity issues.